Evaluation of hematological parameters in patients with CRC in relation to disease recurrence - Roxana Zaharia; Eduard Catrina; Petronel Mustățea; Dragoș Eugen Georgescu; Traian Pătrașcu (Romanian Medical Journal, 2020)
The host's immune response is very important in slowing the progression of the disease in solid cancers. It has a quantitative and a qualitative component, both with an important prognostic role. The aim of this study was to evaluate hematological or biochemical parameters in patients with colorectal cancer in relation to the risk of recurrence. 222 cases of CC and 127 cases of CR (stages I-III accordîng to the AJCC classification edition VIII) were selected and followed for 24 months or until the onset of early recurrence. The patients were hospitalized and undergone surgery in the Dr. I. Cantacuzino Clinical Hospital between 01.01.2015 and 31.12.2017. Following the statistical analysis of the hematological parameters collected preoperatively, a statistically significant association between the neutrophil/lymphocyte ratio and the modified Glasgow score in relation to early recurrence was revealed.